Validation of the Stanford Leisure‐Time Activity Categorical Item (L‐Cat) using armband activity monitor data - Ross, K. M. (Obes Sci Pract, 2018)
OBJECTIVE: Accurate assessment of physical activity (PA) in public health and healthcare settings remains a challenge given limitations of existing brief assessment tools. The Stanford Leisure‐Time Activity Categorical Item (L‐Cat), a single item with six categories, has previously demonstrated excellent reliability and adequate validity relative to pedometer steps. However, pedometers cannot assess key dimensions of PA intensity or duration. METHODS: We evaluated the L‐Cat's criterion validity and sensitivity to change relative to objectively measured Sensewear armband activity monitors among 76 adults with overweight/obesity (mean age 50.8 ± 11.9 years, BMI = 33.1 ± 3.4 kg m(−2)) at baseline and end of a 6‐month behavioural weight management pilot trial. RESULTS: At baseline, L‐Cat category was associated with armband‐measured daily steps (Spearman's ρ = 0.41, p < 0.001), total weekly minutes of moderate/vigorous‐intensity PA (MVPA) (ρ = 0.40, p < 0.001) and weekly minutes of MVPA accumulated in bouts ≥10 min (ρ = 0.47, p < 0.0001). Participants increasing ≥1 L‐Cat category from baseline to 6 months had greater increases in steps (1,110.1 ± 1,852.1 vs. −18.0 ± 2,005.6 steps/d, p = 0.032), total minutes of MVPA (145.7 ± 180.6 vs. −2.1 ± 215.8 min/week, p = 0.007) and greater weight losses (−7.4 ± 7.7% vs. −3.1 ± 4.8%, p = 0.013) than those who stayed the same/decreased L‐Cat categories. CONCLUSION: The L‐Cat demonstrated adequate criterion validity and excellent sensitivity to change relative to objectively measured PA among behavioural weight management pilot trial participants. The L‐Cat may be particularly useful for identifying individuals at lower activity levels and when using all six categories.